Konzept einer agentenbasierten Transportsteuerung: für komplexe, dynamische und multimodale Logistiknetzwerke - Jung, Heiko (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2016)
Transports within industrial logistics networks are planned strategically. Due to the existence of uncertainties an operational control of transports is necessary. Thereby, dispatchers are today not supported adequately. A control approach for dynamic, complex and multimodal transports is developed, which intends to support or automate the operational control. The approach has a decentral and heterarchical organization, in which the goods and means of transports are modeled as agents.